1967
DOI: 10.1083/jcb.33.2.265
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Rna in Mammalian Cells During Mitosis and Interphase

Abstract: Chinese hamster cells in the mitotic and G1 phases of the growth cycle were incubated for 30 or 60 min in suspension tissue culture and pulse-labeled with tritiated uridine. After appropriate chases, washes, and extractions, it was found that all incorporation into the nucleic acid may be accounted for by those cells in interphase. An average of 410 counts was found for incorporation into the cell population (approximately 2.0 x 105 cells) of which over 80% of the cells was initially in mitosis. The increasing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
1

Year Published

1968
1968
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(9 citation statements)
references
References 32 publications
0
8
1
Order By: Relevance
“…Despite the possibility that some genes retain functional RNAP II elongation complexes during M phase, our transcription analyses support the conclusions of others that the majority of RNAP II transcription is repressed during mitosis (5,11,14,18,27,29,36,37,44,55,68). Because run-on transcription assays measure the activity of both transcriptionally active and engaged but paused RNA polymerases, we cannot determine how much of the run-on transcription signals that we observe during mitosis represents active rather than potentially active transcription.…”
Section: Discussioncontrasting
confidence: 65%
See 1 more Smart Citation
“…Despite the possibility that some genes retain functional RNAP II elongation complexes during M phase, our transcription analyses support the conclusions of others that the majority of RNAP II transcription is repressed during mitosis (5,11,14,18,27,29,36,37,44,55,68). Because run-on transcription assays measure the activity of both transcriptionally active and engaged but paused RNA polymerases, we cannot determine how much of the run-on transcription signals that we observe during mitosis represents active rather than potentially active transcription.…”
Section: Discussioncontrasting
confidence: 65%
“…In these studies, it was observed that incorporation of radioactive precursors into nuclear RNA declines in early to mid-prophase and resumes in late telophase. The precise degree of mitotic transcription repression remains uncertain, with some studies detecting mitotic RNA synthesis at 16 to 24% of interphase levels (22,27,29,80). In addition, it is not clear to what degree transcription by each of the three nuclear RNA polymerases (RNAPs) is repressed during mitosis.…”
mentioning
confidence: 99%
“…These studies demonstrated that RNA and protein synthesis varies during the cell cycle, with a sharp decrease in both taking place during mitosis [35]. The transcriptional down-regulation is thought to be due to chromosome condensation [36], the decrease in translation is due to the switch from cap-dependent to cap independent translation [37]. This change is mediated by inhibiting components of cap dependent initiation of translation, eIF4E and eIF4B [37,38**].…”
Section: Cell Cycle Regulated Growth In Mammalian Cellsmentioning
confidence: 99%
“…In addition to chromosome reshaping, mitotic chromosomes are characterized by the disassociation of numerous proteins including RNA polymerase II and many gene-specific and general transcription factors (Martinez-Balbas et al 1995;Parsons and Spencer 1997;Kadauke and Blobel 2013). The disassociation of these transcription machinery components leads to a dramatic decrease in transcription (King and Barnhisel 1967;Gottesfeld and Forbes 1997;Liang et al 2015;Palozola et al 2017).…”
Section: Introductionmentioning
confidence: 99%